2020
DOI: 10.1155/2020/7054534
|View full text |Cite
|
Sign up to set email alerts
|

Pituranthos chloranthus Oil as an Antioxidant-Based Adjuvant Therapy against Cisplatin-Induced Nephrotoxicity

Abstract: The therapeutic outcome of cisplatin is limited due to its adverse side effects in normal tissues. Despite its potent antineoplastic effect, cisplatin is known by a relevant collateral action, for instance, acute renal failure. The aim of this study was to assess the effectiveness of Pituranthos chloranthus (PC) essential oil for contracting cisplatin-induced toxicity, in Balb/c mice. The standard mouse model of cisplatin-induced acute kidney injury (AKI), consisting of one intraperitoneal injection of cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This led to several alterations in the membrane structure and activities of the cell and causes DNA damage, cytotoxicity, and eventually cell death 48 . Our data were consistent with previous work that indicated a significant increase in MDA levels among CDDP-challenged mice 49 . Additionally, the highly increased MDA was due to the CDDP-induced lipid peroxidation and damage of the plasma membrane exerting oxidative stress 48 .…”
Section: Discussionsupporting
confidence: 93%
“…This led to several alterations in the membrane structure and activities of the cell and causes DNA damage, cytotoxicity, and eventually cell death 48 . Our data were consistent with previous work that indicated a significant increase in MDA levels among CDDP-challenged mice 49 . Additionally, the highly increased MDA was due to the CDDP-induced lipid peroxidation and damage of the plasma membrane exerting oxidative stress 48 .…”
Section: Discussionsupporting
confidence: 93%
“…The current research showed that MDA levels in the kidney homogenates of rats administered intraperitoneal CDDP with 12 mg/kg body weight have been significantly upregulated with p < 0.001 in comparison to the control group (Table 2). These data were consistent with previous work that indicated a significant increase with a P-value of < 0.001 in MDA levels in CDDP-challenged mice 49 .…”
Section: Malondialdehyde (Mda)supporting
confidence: 93%
“…Our findings were comparable to the work that was done by Nabavi et al 50 which showed that antioxidant pre-treatments might improve NaF-induced nephrotoxicity in rats by direct scavenging of free radical and/or enhancing the endogenous antioxidant systems. GA showed antioxidant effects by directly free radicals scavenging or by indirectly increasing the antioxidant enzymes activity and expression 49,51 . In addition, GA@CMLMWC uptake exerted excellent biological activities in comparison to those of GA or CMLMWC alone.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous traditionally used herbs were reported to ameliorate cisplatin’s adverse effects, especially hepato- and reno-toxicities, such as Dendropanax morbiferatea [ 19 ], ginger [ 20 ], marjoram [ 6 ], grape seed [ 21 ] and pomegranate rind [ 22 ]. Volatile oils of nigella [ 23 ], fennel [ 24 ] and Pituranthos chloranthus [ 25 ] have been proven to counteract cisplatin-induced renal and hepatic toxicities. Moreover, various phytochemicals demonstrated reno-and hepato-protective effects such as linalool [ 7 ], thymoquinone [ 26 ], cinnamic acid and its derivatives [ 10 , 27 , 28 , 29 ] as well as some flavonoids [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%